RARE-EARTH DIFFUSION IN ZIRCON - Cherniak D.J.; Hanchar J.M.; Watson E.B. (My University, 1997)
Diffusion rates for three rare-earth elements (REEs: Sm, Dy, Yb) have been measured in synthetic and natural zircon. REE-phosphate powders were used as the source of diffusant, with Rutherford backscattering spectrometry (RBS) used to measure REE depth profiles.Over the temperature range 1150-1400°C, the following Arrhenius relations were obtained (diffusion coefficients in m2 s-1):log DYb = (7.40 +/- 1.15) + (-769 +/- 34 kJ mol-1/2.303 RT)log DDy = (5.36 +/- 0.21) + (-734 +/- 35 kJ mol-1/2.303 RT)log DSm = (8.46 +/- 1.61) + (-841 +/- 57 kJ mol-/2.303 RT)Results for synthetic and natural zircons were quite similar, and no evidence of significant anisotropy was observed when comparing transport normal and parallel to the c-axis.The data show a systematic increase in diffusivity with decreasing ionic radius (i.e. faster diffusion rates for the heavier REEs). Given these trends, the diffusion rates of Lu and La should differ by over two orders of magnitude. Diffusive fractionation is unlikely in the Sm-Nd system because differences in diffusivities are relatively small, but may be a factor in the Lu-Hf system given the much slower diffusion rates of tetravalent cations.The very slow diffusion rates measured for the REEs suggest that they are essentially immobile under most geologic conditions, thus permitting the preservation of fine-scale chemical zoning and isotopic signatures of inherited cores.
Keywords: RARE EARTH; DIFFUSION; ZIRCON